Educación religiosa escolar en perspectiva liberadora (2015)
Religious education in Colombia, according to Law 115 of 1994, is an area of fundamental training. However, its purpose of promoting the religious dimension of human beings and understanding the role of religion in culture is far from being achieved, because, in practice, it is considered as an area of second order, is disjointed from the curriculum and is still working as the “religion lesson” of the past. What to do against this? Could it be another way of thinking about religious education? We estimate that, as presuppositions and motivations of both liberation theology and liberating pedagogy are still valid today, they may provide clues in this respect. Consequently, this paper not only makes a detailed reading of this reality in some official educational institutions in Colombia, but also sheds light for the school religious education (ERE) to be liberating.